Efesiensi Pemasaran Sawi Hijau - Saputro, Eko; Widyantari, Ineke Nursih; Nahumury, Marthen A.I. (Musamus University, 2020)
This study aims to analyze the efficiency of the Sawi market in Rimba Jaya Village. The population in this study were 120 farmers and the sample size was 55 farmers. The data are analyzed qualitatively by looking at the marketing channels in order to obtain marketing margins and profits. The results showed that there were four marketing channels used by farmers in Rimba Jaya Village in marketing green mustard, including: Marketing channel 1, namely from farmers - retailers. Marketing channel 2, namely from farmers - middle traders - retailers - consumers. Marketing channel 3, namely from farmers - wholesalers - middle traders - retailers - end consumers. Marketing channel 4, namely from farmers - village collectors - wholesalers - retailers - end consumers. The four marketing channels, all marketing channels, are said to be efficient, because their marketing efficiency is more than 0 and less than 1, but the most efficient is found in marketing channel 4 and is in large traders' institutions which have the smallest marketing efficiency value of 0, 02. Keywords: Marketing, Green Mustard, Marketing Efficiency